Failure of sintered carbide cutting tools under variable amplitude fatigue - Altan, E; Ünal, A (MINERALS, METALS & MATERIALS SOC, 1996)
The failure of sintered carbide cutting tools is one of the most important problems in automating the manufacturing system and evaluating the optimal cutting conditions. Previous efforts to apply the fracture concept has been devoted to the study of brittle failure mechanics and to the determination of the fracture strength of tool materials. In this study, the failure of sintered carbide cutting tools, P20, P40, K10, K20 grades, has been analysed under constant and variable amplitude fatigue by using different loading sequences. Failure of sintered carbide by fatigue cracking has been observed by using plane bending tests on specimens. A model of the failure of sintered carbide cutting tools under constant and variable amplitude fatigue depending on the strain hardening of the Co binder and the growth of the crack has been developed. The experimental results showed that cutting under the variable amplitude loading gives different times to failure depending on the sequence of loading amplitude. A loading sequence which has high and then subsequently Low amplitude gives longer times to failure than a low and subsequently high amplitude sequence. It means that in interrupted sequential cutting operations it is possible to increase the time to failure by choosing suitable cutting conditions and the correct sequence of cutting.
Keywords: CRACK-GROWTH; Engineering; Metallurgy & Metallurgical Engineering